Pengaruh Tingkat Pendidikan Pemilik, Praktik Akuntansi dan Persepsi atas Insentif Pajak Terhadap Kepatuhan Perpajakan UMKM - Putri Zainal, Rr Fauziah Nur Rahmasari; Perdana, Petrolis Nusa; Musyaffi, Ayatulloh Michael (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are one of the sectors that have the potential to contribute to the state revenue. However, tax compliance among MSMEs is still very low, especially in the tax compliance of MSMEs in the East Ciputat District. The purpose of this study is to determine the influence of the owner's educational level, accounting practices, and perceptions of tax incentives on MSMEs' tax compliance. A total of 100 Individual Taxpayers of MSMEs were selected as respondents using the slovin formula. The sample determination method in this study is probability sampling through simple random sampling, and the technical analysis of the research data uses inferential statistics with the help of SmartPLS 4.0 (Partial Least Square) program. The results show that the owner's educational level, accounting practices, and perceptions of tax incentives significantly and positively influence MSMEs' tax compliance.